SISTEM PENGISIAN JABATAN KEPALA DAERAH DI INDONESIA MENURUT ASAS OTONOMI DAERAH - Saddam Bancin; Faisal Akbar Nasution; Mirza Nasution; Pendastaren Tarigan (Universitas Sumatera Utara, 2017)
ABSTRACT The principle of regional autonomy spawned legal norms stating that based on the principle of regional autonomy, regional head position the charging system is done through an election by the people of the area, and without the participation of the central government in determining the position of head of the area. According to the principle of regional autonomy, local independently determine the head region. Then, Indonesia as a state constitutional establish legal order based on the provisions of the constitution. An Act to regulate the charging system regional head position is formulated to maintain consistency with the provisions of the constitution. The rule of law charging system based regional head position is a reflection of democracy and the constitutional principle of local autonomy simultaneously. Based on the principle of local autonomy, the territory can apply the rule of law different charging systems associated with regional head position. These different settings later called asymmetric decentralization system of filling the position of regional head. The asymmetric decentralization can not only be applied to areas that are privileged and special, but also can be applied to areas in general. Keywords : Legal Structure, Local Autonomy Principle, Head of Local Govern, Asymmetric Decentralization